STAT3 Contributes to Radioresistance in Cancer - Wang, Xuehai; Zhang, Xin; Qiu, Chen; Yang, Ning (Frontiers in Oncology, 2020)
Radiotherapy has been used in the clinic for more than one century and it is recognized as one of the main methods in the treatment of malignant tumors. Signal Transducers and Activators of Transcription 3 (STAT3) is reported to be upregulated in many tumor types, and it is believed to be involved in the tumorigenesis, development and malignant behaviors of tumors. Previous studies also found that STAT3 contributes to chemo-resistance of various tumor types. Recently, many studies reported that STAT3 is involved in the response of tumor cells to radiotherapy. But until now, the role of the STAT3 in radioresistance has not been systematically demonstrated. In this study, we combine an updated understanding of STAT3 with a review of current studies regarding the role of STAT3 in mediating radioresistance.